2021
DOI: 10.1186/s12967-021-02934-y
|View full text |Cite
|
Sign up to set email alerts
|

Dipstick proteinuria and risk of type 2 diabetes mellitus: a nationwide population-based cohort study

Abstract: Background Proteinuria has been recognized as a marker of systemic inflammation and endothelial dysfunction associated with insulin resistance and β-cell impairment, which can contribute to the development of type 2 diabetes mellitus (T2DM). However, it is unknown whether the dipstick proteinuria test has a predictive value for new-onset T2DM. Methods This retrospective cohort study analyzed 239,287 non-diabetic participants who participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Secondary level facilities reported a fair average readiness in basic equipment (90%) while primary facilities (70%) lagged slightly behind as indicated by the study findings. This represents an increase of readiness of diabetes specific tracer equipment compared to findings reported by the Kenya Harmonized Facility Assessment (KHFFA) 2018/2019 study that reported a 63 percent readiness [ 36 ]. Notable gaps were however reported that require intervention especially in regards to blood glucometer machine and strip at primary level facilities (45%) and weighing scale digital at secondary level (82%).…”
Section: Discussionmentioning
confidence: 80%
“…Secondary level facilities reported a fair average readiness in basic equipment (90%) while primary facilities (70%) lagged slightly behind as indicated by the study findings. This represents an increase of readiness of diabetes specific tracer equipment compared to findings reported by the Kenya Harmonized Facility Assessment (KHFFA) 2018/2019 study that reported a 63 percent readiness [ 36 ]. Notable gaps were however reported that require intervention especially in regards to blood glucometer machine and strip at primary level facilities (45%) and weighing scale digital at secondary level (82%).…”
Section: Discussionmentioning
confidence: 80%
“…Another study revealed that the risk of Type 2 diabetes mellitus increased with the severity of proteinuria. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%